Performance of an advanced heat recovery ventilation system in the Canadian Arctic. Issue 3 (8th December 2021) - Berquist, Justin; Banister, Carsen; Krys, Dennis
Abstract: A demonstration house was previously built and commissioned in Iqaluit, Nunavut, Canada. The purpose of the overall effort is to develop and integrate technologies and evaluate the performance of a high-performance building located in the Canadian Arctic, while considering the unique social, economic, and logistical challenges associated with its remote location. Previous work consisted of monitoring and reporting on the energy use from heating between April 2016 and April 2017. The purpose of this next stage of research is to contribute experimental data of the prototype demand-controlled residential ventilation system in the extremely cold climate of Iqaluit, where the average annual outdoor temperature is approximately −9 °C. This paper outlines the development, implementation and monitoring of the carbon dioxide-based demand-controlled heat recovery ventilation system that took place between April 2017 and April 2019. The system was equipped with two electric preheaters to ensure that frost build-up did not occur in the heat recovery ventilator (HRV) and adequate ventilation could be maintained according to the demand. An electric heater was included after the HRV to control the supply air temperature. Between December 2018 and February 2019 the electricity consumption of the HRV, preheaters, and supply air heater were measured for the lowest ventilation rate of the system, 15.5 L/s. Pertinent temperatures in the ventilation system were also monitored to enable assessment of the system's performance. A comparison of the sensible recovery efficiency (SRE) of the HRV and overall system is presented. Experiments displayed that, on average, the SRE of the HRV and system were 72% and 35%, respectively. The total energy use of the ventilation system was 390 kWh over the two months, which translates to 6.30 kWh/day, an energy use intensity of 0.27 kWh/m 2 /day, or 12.25 Wh/m 3 of outdoor air supplied.